Do psychological inflexibility and self-criticism mediate the relationship between depression and addiction severity? - Ulusoy, Sevinç; Ramakan, Enver Denizhan; Güleç, Veysel; Alnıak, İzgi; Yavuz, Kaasım Fatih (Kare Publishing, 2022)
Objective: Self-related problems and psychological inflexibility, which can also lead to a vulnerability to depression, often accompany substance use disorders. This study examined whether psychological inflexibility and self-criticism mediated the relationship between depression and addiction severity. Method: We examined 111 patients with Substance use disorders (SUDs) using the Addiction Profile Index (API), Beck Depression Inventory (BDI), Forms of Self-criticizing/Attacking and Self-reassuring Scale (FSCRS), and Acceptance and Action Questionnaire-Substance Abuse (AAQ-SA). Mediation analysis was conducted to examine the mediating role of psychological inflexibility on the relationship between depression and addiction severity. Results: API total score was negatively correlated with AAQ-SA and positively correlated with BDI and FSCRS. Because FSCRS did not have a significant predictive effect on addiction severity (p=0.966), only AAQ-SA was included in the mediation analysis. According to the results of the mediation analysis, depression was found to directly affect addiction severity (direct effect, p=0.007), and it constitutes 54.5% of the total effect. Also, depression predicted addiction severity (indirect effect, p<0.001) through psychological flexibility, and it constitutes 45.5% of the total effect. Conclusion: According to our findings, psychological inflexibility is an important variable between depression and addiction severity. Although patients with SUDs may have negative evaluations about self, they may not use self-criticism as a coping strategy. Psychological inflexibility may be a substantial target for interventions in patients who use substances to avoid depressive symptoms.
Keywords: Experiential Avoidance; Depression; Psychological Inflexibility; Self-Criticism; Substance Use Disorders